PREVENTIVE REGULATIONS TO REMOVE ENVIRONMENTAL DAMAGE TO MANGROVE ECOSYSTEM AT EAST KALIMANTAN, INDONESIA - Kotijah, Siti; Ventyrina, Ine (Faculty of Law Universitas Panca Bhakti, 2019)
Indonesia is an archipelago state composed with thousands of large and small islands. Mangrove restoration got widespread attention given the high economic and social value of ecosystem ecology. Restoration may raise the value of mangrove biodiversity resources, give the livelihoods of the population, prevent damage to the beach, keepbiodiversity, fisheries, and others. This paper proposes legal frameworks to support to counteract damage to mangrove ecosystem at East Kalimantan based on Indonesian regulations.